ANALISIS ARSITEKTUR BANGUNAN KOLONIAL EKS KANTOR BUPATI KOLAKA PERTAMA KELURAHAN LATAMBAGA KECAMATAN LATAMBAGA KABUPATEN KOLAKA PROVINSI SULAWESI TENGGARA - Andi Rajab Putra; sitti kasmiati (SANGIA JOURNAL OF ARCHAEOLOGY RESEARCH, 2018)
The building of the former regent's office was the first building that was facing the historical area of the district ofKolaka. This building is expected to be made in the early 1920s.The purpose of this study was to determine thecharacteristics and architectural style of the building of the former Kolaka regent's office. The problems of this thesisare, first, what are the characteristics of the building of the former Kolaka regent'soffice and what is the architecturalstyle of the former Kolaka regent's office building. This study uses the theory of understanding architecture ingeneral, tropical architecture, and various types of colonial architecture in Indonesia used in answering researchproblems. The results showed that the building of the former Kolaka regent's office had characteristics of differentand very simple buildings such as doors, windows, air venilations in the front view of the building having the samepattern and shape while the architectural style of the former regent's office building was influenced by architecturalstyles. The Netherlands from the 1920s to the 1940s due to the direction facing the front of the building towards theWest, the rear side facing northof the building, windows, doors, large air vents aimed at maximizing air circulation inthe building